Molecular Demonstration of a Pneumocystis Outbreak in Stem Cell Transplant Patients: Evidence for Transmission in the Daycare Center - Robin, Christine; Alanio, Alexandre; Gits-Muselli, Maud; la Martire, Giulia; Schlemmer, Frédéric; Botterel, Françoise; Angebault, Cécile; Leclerc, Mathieu; Beckerich, Florence; Redjoul, Rabah; Pautas, Cécile; Toma, Andrea; et al. (Frontiers in Microbiology, 2017)
Pneumocystis jirovecii pneumonia (PCP) is a life-threatening infection in hematology. Although occasionally reported, the role of interhuman transmission of P. jirovecii in PCP, compared to that of reactivation, remains an unresolved question; the recommendation to isolate PCP patients in the hematology ward are not well evidence-based. Following an unexpected increase in the number of febrile pneumonia patients with P. jirovecii DNA detected in respiratory samples in our hematology ward, we explored 12 consecutive patients from November 2015 to May 2016. Genotyping of P jirovecii was performed using microsatellite markers. The frequency of simultaneous occupancy of these 12 patients in the same unit on the same day from four months prior to the first diagnosis was recorded. In three patients, the P. jirovecii genotype could not be determined because DNA was insufficient. One rare single genotype (Gt2) was found in four of the other nine, all allogeneic stem cell transplant recipients. The transmission map showed that these four patients had multiple opportunities to meet on the same day (median, 6.5; range, 4-10) at the daycare center. It was much less among the eight non-Gt2 patients (median, 1; range, 0-9; P = .048). This study, based on modern molecular technics, strongly suggests that interhuman transmission of P. jirovecii between allogeneic stem cell transplant recipients is possible. P. jirovecii DNA detected in respiratory specimens supports that isolation and respiratory precautions be recommended in such cases in the hematology ward.